PELUANG EKSPOR ARANG TEMPURUNG KELAPA INDONESIA DI PASAR INTERNASIONAL TAHUN 2020-2021 - ", Nurhafika; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This is research aims to explain the export opportunities of Indonesian coconut shell charcoal in the international market in 2020-2021 seeing that coconut shell charcoal is a sub-sector of plantation products, namely coconut (coconut) which has the potential to be exported to international markets and can increase the country's foreign exchange. Constraints in the export of Indonesian coconut shells are the lack of raw materials for the manufacture of shell charcoal and traditional manufacturing methods and even the lack of knowledge of international market access while the demand for coconut shell charcoal from abroad continues to increase. This research was obtained from books, journals, official documents and websites that support the hypothesis. The author uses the liberalism perspective of Adam Smith, the level of analysis of the Nation-State and the theory used in this research is the theory of interdependence. The results of this study indicate that in order to increase exports, the government makes the Triple Exports Movement (Gratieks) program to accelerate the increase in the volume and or value of exports of plantation products, as well as to compete and win the world export market.Â Keywords : Export of Coconut Shell Charcoal, International Market, Triple Export Export Movement (Gratieks).